(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This article explores the pragmatic features of verb types in English and Uzbek, with a particular focus on the interaction between action and stative verbs in literary discourse. Drawing on selected English and Uzbek literary works, the study analyzes how verb choice shapes communicative intent, contextual meaning, character depiction, and narrative dynamics. The comparative approach identifies structural, functional, and pragmatic parallels and divergences between the two languages. The findings demonstrate that verbs not only express action or state, but also play a crucial role in constructing social relationships, expressing modality, indicating evidentiality, and managing discourse.